Mercy road [videorecording (DVD)] - Curran, John; Heffring, Jesse; Pelletier, Chris; Bracey, Luke, 1989-; Jones, Toby, 1966- (Well Go USA Entertainment, 2023)
After committing an impulsive, vicious crime while searching for his missing daughter, a frantic father goes on the run from law enforcement and soon begins receiving chilling calls from an unknown entity claiming to know her whereabouts. As he faithfully follows the caller's increasingly unhinged instructions, he is driven perilously close to the edge of sanity while discovering exactly how far he is willing to go to save his child.